Methadone maintenance-lessons from two systems in China - Shui-Shan Lee; Robert Newman (BMC, 2017)
Abstract In Hong Kong, methadone maintenance treatment (MMT) was launched in the 1970s, almost 30 years before the counterpart programme's inauguration in Mainland China. Both were established in response to perceived public crises-addiction-related crime and HIV outbreak, respectively-and both are now regular services under two systems in the same country. Effectiveness of MMT in achieving the stated goals was evident in each case and provides useful lessons on strategies for dealing with the varied concerns related to illicit drug use. Today, with changing patterns of drug addiction, increasing competition for resources, and changing attitudes towards addiction and its treatment, the two MMT systems are confronted with similar challenges to achieve sustainability.